1979
DOI: 10.1111/j.1748-1716.1979.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vasoactive intestinal polypeptide on blood flow, motility and fluid transport in the gastrointestinal tract of the cat

Abstract: The effect of close intraarterial infusions of vasoactive intestinal polypeptide (VIP) on gastric motility, intestinal fluid transport and colonic motility were studied in the cat. Regional blood flow was also followed in all experiments. In the stomach VIP produced a gastric relaxation and a blood flow increase. The motility response was similar to that observed when eliciting the vago-vagal reflex relaxation by distending the esophagus. In the small intestine a hyperemia and a decrease of net water uptake wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(27 citation statements)
references
References 14 publications
(9 reference statements)
0
26
1
Order By: Relevance
“…Intrarenal nerves immunoreactive for substance P, vasoactive intestinal peptide and calcitonin gene-related peptides have been reported (Barajas et al, 1983;Ferguson and Bell, 1985; Su et al, 1986), but the relative densities of peptidergic nerves on different parts of the arterial tree have not been thoroughly studied. Whether each peptide is synthesized by a separate nerve population or coexists with other peptides or with catecholamine, and whether each is contained in sensory or autonomic nerves are points of interest that require further study.Immunohistochemical methods have been used to visualize vasoactive intestinal peptide (VIP) in both central and peripheral neurons, including those that innervate the heart and blood vessels where it is released by nerve stimulation and probably causes vasodilation (Della et al, 1983;Eklund et al, 1979;Heistad et al, 1980;Jarhult et al, 1980;Shimizu and Taira, 1979). Although several workers failed to detect VIP-immunoreactive (VIPI) nerves in pig, cat, rat, mouse, and guinea pig kidneys (Alm et al, 1980;Larsson et al, 1977;Uddman et al, 1981), Hokfelt et al (1978) showed that VIPI nerves innervate arteries in the guinea pig renal cortex, and Forssman et al (1982) found such nerves in kidneys of the guinea pig, rat, cat, dog, pig, and Tupaia and 0 1987 ALAN R. LISS, INC. noted that intrarenal distribution is subject to species variation.…”
mentioning
confidence: 99%
“…Intrarenal nerves immunoreactive for substance P, vasoactive intestinal peptide and calcitonin gene-related peptides have been reported (Barajas et al, 1983;Ferguson and Bell, 1985; Su et al, 1986), but the relative densities of peptidergic nerves on different parts of the arterial tree have not been thoroughly studied. Whether each peptide is synthesized by a separate nerve population or coexists with other peptides or with catecholamine, and whether each is contained in sensory or autonomic nerves are points of interest that require further study.Immunohistochemical methods have been used to visualize vasoactive intestinal peptide (VIP) in both central and peripheral neurons, including those that innervate the heart and blood vessels where it is released by nerve stimulation and probably causes vasodilation (Della et al, 1983;Eklund et al, 1979;Heistad et al, 1980;Jarhult et al, 1980;Shimizu and Taira, 1979). Although several workers failed to detect VIP-immunoreactive (VIPI) nerves in pig, cat, rat, mouse, and guinea pig kidneys (Alm et al, 1980;Larsson et al, 1977;Uddman et al, 1981), Hokfelt et al (1978) showed that VIPI nerves innervate arteries in the guinea pig renal cortex, and Forssman et al (1982) found such nerves in kidneys of the guinea pig, rat, cat, dog, pig, and Tupaia and 0 1987 ALAN R. LISS, INC. noted that intrarenal distribution is subject to species variation.…”
mentioning
confidence: 99%
“…The present findings suggest that a local PYY release would lead to, for example, a decrease in blood supply and colonic smooth muscle tone. Thus, PYY has actions opposite to those of local vasodilating and smooth muscle contracting factors present in the intestinal mucosa, such as vasoactive intestinal polypeptide (14,15) and substance P (16)(17)(18). In fact, in the submandibular salivary gland, PYY inhibits the atropine-resistant vasodilatation induced by parasympathetic nerve stimulation as well as the blood flow increase inducedby vasoactive intestinal polypeptide infusions (unpublished findings).…”
mentioning
confidence: 99%
“…After rinsing in sucrose and cryostat sectioning, the tissues were processed as described (9). Briefly, the sections were incubated in a humid atmosphere at 4°C for [14][15][16][17][18][19][20] In vivo experiments were performed in six cats anesthetized with chloralose (50 mg/kg) and urethane (100 mg/kg). Intestinal blood flow was recorded via a polyethylene catheter in the superior mesenteric vein connected to a closed silicone-filled drop chamber.…”
mentioning
confidence: 99%
“…Several authors speculated that VIP has a regulatory effect on transport of water and electrolytes, or on vasodilation (Barbezat et al, 1971;Eklund et al, 1979;Fahrenkrug et al, 1978;Krejs et al, 1978;Racusen and Binder, 1977;Schwartz et al, 1974;Thulin and Olsson, 1973). The presence of a number of VIPLI fibers in the lamina propria, particularly along the blood vessels of the stomach, supports these concepts.…”
Section: Discussionmentioning
confidence: 96%